Development of E-Worksheet Project-Based Learning on Green Chemistry Materials to Improve Students Creative Thinking Skills - Janah, Shafna Nor; Hidayah, Rusly (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Creative thinking skills are one aspect of high-level thinking skills that students must have in 21st-century learning. Based on PISA 2022 data, the creative thinking skills of students in Indonesia are still relatively low. Therefore, this study aims to describe the feasibility of a project-based e-worksheet on green chemistry material to improve students' creative thinking skills. The type of research is Research and Development (R&D) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Validity data is obtained from the validator's assessment using a validation questionnaire sheet. Practicality data is obtained from the results of the learner response questionnaire, which is supported by the results of observations of learner activities and observations of learning implementation. Practicality data is obtained from the results of the pretest and posttest of students' creative thinking skills. The validation results show that the content validity and construct validity of the e-worksheet are declared valid with mode 4. Practicality in terms of student questionnaire responses shows a very practical category with a material clarity percentage of 95.7%, ease of use of 100%, and usability of the e-worksheet of 100%. The effectiveness results are reviewed from the results of the N-gain score pretest and posttest of creative thinking skills in high categories. The N-gain on each indicator of fluency, flexibility, originality, and elaboration was 0.84, 0.82, 0.79, and 0.86. The results showed that a project-based e-worksheet on green chemistry material is feasible to use as a solution to improve students' creative thinking skills.